The cemetery of untold stories : a novel [large type] - Alvarez, Julia (Thorndike Press large print top shelf., 2024)
"When celebrated writer Alma Cruz inherits a small plot of land in the Dominican Republic, she turns it into a place to bury her untold stories--literally. She creates a graveyard for manuscript drafts and revisions and the characters whose lives she tried but failed to bring to life and who still haunt her. Alma wants her characters to rest in peace, but they have other ideas, and the cemetery becomes a mysterious sanctuary for their true narratives."--Provided by publisher